Orbital transfers in an asteroid system considering the solar radiation pressure - Oliveira, Geraldo Magela Couto; Bertachini de A. Prado, Antonio F.; Sanchez, Diogo Merguizo; Gomes, Vivian Martins [UNESP] (Springer Nature, 2017)
The present paper studies the effects of the radiation pressure in the trajectories of a spacecraft in transfers between the collinear Lagrange points of a double asteroid system. The system considered is this paper is formed by the double asteroid 1996FG3 and the maneuvers are always assumed to be bi-impulsive. In a system formed by asteroids, the solar radiation pressure has a significant influence in the transfers paths. This occurs because the gravitational forces in these systems are smaller if compared with systems formed by larger bodies. Solutions with lower and higher fuel consumption can be found by adding the solar radiation pressure. The radiation pressure was not used as a control but its effects over the transfers were measured. For a small system of primaries such as an asteroid system, it is very important to take into account this force to make sure that the spacecraft will reach the desired point.
Keywords: Astrodynamics; Double asteroids; Lagrange points; Orbital transfers; Solar radiation pressure